KREATIVITAS GURU AKIDAH AKHLAK DALAM MENCIPTAKAN PEMBELAJARAN YANG EFEKTIF DAN MENYENANGKAN - Yeri Utami; Siti Ma'rifatuz Zahroh (PERMAI: Jurnal Pendidikan dan Literasi Madrasah Ibtida'iyah, 2022)
Teacher creativity is needed in the learning process to be able to create an effective and pleasant learning atmosphere, so that the goals of education can be achieved optimally. This study aims to describe the creativity of Akhidah Akhlak teachers in creating an effective and fun learning atmosphere for grade 1 students of MI Muhammadiyah Tambaksari Blora Regency in 2022. This research uses descriptive qualitative research with field research design. Data collection in this research was carried out using observation, interview, and documentation techniques. The results concluded that Akhidah Akhlak teachers at MI Muhammadiyah Tambaksari already have indicators of teachers who have creativity. In creating effective learning, the things the teacher does include: 1) Using an interactive whiteboard or LCD projector to display photos, video displays, and activities that encourage students to experiment and be active in class, 2) conduct scientific experiments and act out short dramas in class, 3) giving question-based instructions can focus students' attention on the lesson or material being discussed, 4) using an interactive whiteboard / LCD to display images and videos that can help students visualize the material being studied. Meanwhile, in creating fun learning, teachers do the following: 1) Greeting students in a friendly and enthusiastic manner, 2) Creating a relaxed atmosphere, 3) Motivating students, 4) Using ice breaking, 5) Using varied methods.Keywords: Teacher Creativity, Effective Learning, Fun Learning